[PP.25.17] THE AA2-RATIO: IMPROVED SCREENING FOR PRIMARY ALDOSTERONISM IN HYPERTENSION. (September 2016) - Poglitsch, M.
Abstract : Objective: The prevalence of hypertension in Europe is 30% among the adult population, affecting estimated 119 million people in in 2015. Numbers of hypertensive patients are constantly growing and an increase by 15% till 2025 is estimated. Up to 11, 9 million people in Europe are referred to be resistant hypertensive. Primary aldosteronism (PA) is a frequent form of resistant hypertension affecting up to 20% of resistant hypertensive patients, up to 2, 4 million Europeans. Design and method: PA can be can be cured by appropriate second-line drug treatments or surgical procedures, if detected. Recommendations of clinical societies suggest extensive screening efforts to facilitate the early detection of PA among resistant and high-risk hypertensive patients in order to reduce cardiovascular events. However, actual clinical practice does not adhere to these guidelines due to the lack of appropriate screening procedures. A major issue in the diagnostic process of PA is that standard tests interfere with anti-hypertensive therapies, which needs to be discontinued before testing. This imposes a severe cardiovascular risk to affected patients, which is usually not taken by physicians leading to poor adherence to clinical guidelines. Results: Despite strong limitations regarding selectivity and the interference with multiple anti-hypertensive drugs, the antibody-based determination of the aldosterone-renin-ratio (ARR) is widely used for PA case detection. However, there is still a strong demand for accurate and reliable and patient friendly PA case detection. The Aldosterone-to-Angiotensin-II-Ratio (AA2-Ratio) is a novel LC-MS/MS based high-throughput test for PA that utilizes the plasma levels of aldosterone and physiologically active angiotensin II to generate a diagnostic ratio. Conclusions: The availability of an innovative diagnostic approach (RAS-Equilibrium-Analysis) paved the way for angiotensin peptides to be used in clinical routine testing by solving pre-analytic problems of analyte stability. The test performance is superior to state-of-the-art tests in terms of the size of the diagnostic window and method accuracy. Importantly, the AA2-Ratio does not interfere with standard anti-hypertensive drugs including ACE inhibitors. First data obtained in a proof-of-concept study proved the AA2-Ratio to be a versatile and powerful diagnostic tool for the diagnosis of PA in hypertension.